2006
DOI: 10.1021/es061099y
|View full text |Cite
|
Sign up to set email alerts
|

Communication of Radiation-Induced Stress or Bystander Signals between Fish in Vivo

Abstract: We report data in this paper suggesting that fish irradiated to 0.5 Gy total body dose can release factors into the water that signal other unexposed fish and cause induction of bystander effects expressed as increased cell death in a reporter system. Radiation-induced bystander effects, resulting in the appearance of radiation damage or induction of typical radiation responses in unirradiated cells and tissues are now an established consequence of exposure to low doses of ionizing radiation, however little wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
61
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 39 publications
15
61
0
1
Order By: Relevance
“…These findings have been previously reported by various groups such as Mothersill et al (2005Mothersill et al ( , 2006Mothersill et al ( , 2007 and O 'Dowd et al (2006) which have shown the production of bystander factor(s) after in vivo and in vitro irradiation of various species of mice and fish.…”
Section: Discussionsupporting
confidence: 86%
“…These findings have been previously reported by various groups such as Mothersill et al (2005Mothersill et al ( , 2006Mothersill et al ( , 2007 and O 'Dowd et al (2006) which have shown the production of bystander factor(s) after in vivo and in vitro irradiation of various species of mice and fish.…”
Section: Discussionsupporting
confidence: 86%
“…Manifold evidence indicates that blood vessels and their different repair efficiencies in malignant and healthy tissue are essential to explain the differential effect of microbeams 2 , 4 , 5 , 13 . Apart from that experiments demonstrate that bystander signals, 14 , 15 changes in the immune response, DNA repair, and variations in the cell cycle 16 are important for the biological response to MRT.…”
Section: Introductionmentioning
confidence: 99%
“…a tissue in direct contact with any radiation induced bystander signal present in the water) was then removed at the peduncle and placed in ice cold L15 tissue culture medium. Explant cultures of these fin samples were made by firstly incubating segments of tissue (approximately 1 mm 2 ) in 0.25% w/v trypsin (Gibco, Biocult, Irvine, Scotland) for 30 min at 19 C. After trypsin treatments the tissue segments were placed in the centre of T25 cell culture flasks (NUNC, Uden, Denmark) in 2 ml RPMI-1640, supplemented as described (Mothersill et al, 2006). These explants were then incubated for 48 h at 19 C. After 48 h the explant media was collected, filtered and transferred to cultures of the HPV-G reporter cells.…”
Section: Bystander Effect Induction Tissue Collection and Clonogenicmentioning
confidence: 99%
“…There is now an increasing amount of data to show that fish, when irradiated with low doses of radiation, are able to induce a bystander effect in non-irradiated fish. Predominantly this research has been carried out using 0.5 Gy X-ray irradiation (Mothersill et al, 2012(Mothersill et al, , 2009(Mothersill et al, , 2007(Mothersill et al, , 2006Saroya et al, 2010;Smith et al, 2013Smith et al, , 2011. X-rays have the advantage of not making the irradiated fish radioactive.…”
Section: Introductionmentioning
confidence: 99%